Leveraging contract farming to reduce leafy vegetable waste: a system dynamics approach from Kermanshah province of Iran - Mostafa Moradi; Hossein Shabanali Fami; Ali Akbar Barati; Felicitas Schneider; Reza Salehi Mohammadi; Lusine Aramyan (Cogent Food & Agriculture)
Decreasing food loss and waste (FLW) has become a global concern towards achieving sustainable food systems. One widely embraced approach is contract farming (CF), which enables the supply chain (SC) actors to manage the aggregate SC risks. Leafy vegetables are particularly vulnerable to wastage due to inadequate quality and SC performance, with Iran experiencing an alarming annual leafy vegetables waste (LVW) rate of 39% due to SC inefficiencies. Numerous scholars have proposed diverse FLW prevention strategies, yet their implementation often falters due to the absence of economic incentives for stakeholders. Hence, the focus should shift towards market-based strategies. This study examines the effect of CF as an economic incentive for farmers to reduce LVW in Kermanshah province. To achieve this goal, a system dynamics model of the waste system in the leafy vegetable SC (LVSC) was developed Data for the research was collected using a questionnaire, which surveyed 60 specialists and 728 actors across the SC. The results revealed that more than 50% of the LVW could be reduced by implementing CF. Consequently, government policies and initiatives should prioritize the development of processing industries via CF as a strategic avenue for action.